Pengembangan Media Buku Bantuan Diri untuk Memberikan Pemahaman Bahaya Merokok - Vania Aprilo Livia Hutabarat; Raudah Zaimah Dalimunthe; Putri Dian Conia (Lembaga Pengembangan Kinerja Dosen, 2025)
The study aims to develop self-help book media to understand the dangers of smoking. The method used is Research and Development (R&D) with the development of ADDIE Analysis, design, development, implementation and evaluation). The evaluation was carried out by validators of media experts, materials, language experts and expert practitioners. Based on these data, the results of the evaluation of the validity of media experts were 85%, material experts were 80%, the percentage obtained from language experts was 96.4% and the percentage from practitioners was 84.6%. The average feasibility result was 86.5% with the category